2013
DOI: 10.1128/jvi.01835-13
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Toll-Like Receptor Ligation and Selective Killing of Dendritic Cell Subsets Fail To Dissect Priming Pathways for Anti-Vaccinia Virus CD8+T Cells

Abstract: CD8؉ T cell responses can be generated by direct or cross-priming mechanisms, and several mouse models have been used to reveal which of these is the most important pathway for various viruses. Among these models is systemic treatment of mice with a CpG-containing oligodeoxynucleotide (CpG) to mature all dendritic cells (DCs), rendering them incapable of cross-presentation. A second is the use of cytochrome c (cytc) as a selective poison of the subsets of DCs able to cross-present antigen. In this study, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…In our own studies, it was found that subdominance of the IAV-derived epitopes H2-D b -PB1-F2 62-70 and H2-K b -NS2 [114][115][116][117][118][119][120][121] in the B6 model of IAV infection is associated with the relative paucity of highavidity T cells in the pre-immune and immune repertoires, but not with CTLP numbers or antigen dose 25,38 . In fact, attempts to equalize epitope abundance using a variety of immunization strategies failed to align immune responses with relative CTLP frequency 38 .…”
Section: Expansion Of Naive Ctlp Populationsmentioning
confidence: 93%
See 2 more Smart Citations
“…In our own studies, it was found that subdominance of the IAV-derived epitopes H2-D b -PB1-F2 62-70 and H2-K b -NS2 [114][115][116][117][118][119][120][121] in the B6 model of IAV infection is associated with the relative paucity of highavidity T cells in the pre-immune and immune repertoires, but not with CTLP numbers or antigen dose 25,38 . In fact, attempts to equalize epitope abundance using a variety of immunization strategies failed to align immune responses with relative CTLP frequency 38 .…”
Section: Expansion Of Naive Ctlp Populationsmentioning
confidence: 93%
“…However, this ignores the possibility that these same DC populations might be equally capable of direct presentation 115 . Similarly, paralyzing cross-presentation using systemic maturation of DCs has unanticipated effects on direct presentation, so this tool is not useful for dissecting these pathways 116 . Studies with mice deficient in proteins uniquely required for cross-presentation -for example, interferon-γ-inducible lysosomal thiol reductase (GILT; also known as IFI30) -should offer less complicated interpretations 117 .…”
Section: Box 3 | Endogenous Presentation Versus Cross-presentation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it has been reported that CP dominates the CD8 lymphocyte response to the replication-deficient strain of VACV-modified vaccinia Ankara (Gasteiger et al, 2007). However, this finding has been challenged (Wong et al, 2013).…”
Section: Direct-and Cross-presentation In Antiviral Cd8 T Lymphocyte mentioning
confidence: 99%
“…In vivo, type I IFN may be critical for XPT responses (212). On the other hand, TLR4 and TLR9 agonists can reduce XPT to particulate antigens (163) and systemic administration of TLR-agonists results in a marked inhibition of XPT (213) and possibly direct presentation (214). The stimulatory vs. inhibitory effects of TLR agonists may be influenced by their purity (215).…”
Section: Regulation Of Xptmentioning
confidence: 99%